Canopy facilitates seaweed recruitment on subtidal temperate reefs. (11th August 2014) - Bennett, Scott; Wernberg, Thomas; Nilsson, Christer
Summary Facilitation through physical stress amelioration has been largely overlooked in subtidal marine ecosystems, where abiotic gradients are perceived to be benign. However, seemingly subtle changes in marine environmental conditions can alter community structure across vast areas, and therefore, the type of interactions and any refuge provided by marine foundation species. This could have substantial implications for community organization. We measured net recruitment rates of subtidal seaweeds under experimentally modified canopy densities, across 1000 km of coastline, to examine the nature of interactions between seaweed canopies and recruits. Contrary to expectations, facilitation, as evidenced by higher recruitment under canopies, was observed throughout all conditions for Scytothalia dorycarpa and under partial canopies at three of four locations for Sargassum spp., whilst competitive interactions remained prevalent for Sargassum under closed canopies. Supply side dynamics were also of major importance to recruitment success for Scytothalia. For Sargassum, the interaction strength between recruits and the canopy became increasingly positive towards lower latitudes, suggesting the canopy environment was mitigating stress across the latitudinal climate gradient. Synthesis. Positive interactions and stress amelioration play an important and previously unrecognized role in determining the recruitment success and viability of seaweeds in subtidal marine ecosystems. These results challenge long held paradigms about the general importance of canopy competition and force a rethink of how seaweed interactions affect habitat resilience to disturbances in subtidal ecosystems.